2020
DOI: 10.1158/0008-5472.can-18-3985
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Resistance to HER2-Targeted Therapies Creates Vulnerability to ATP Synthase Inhibition

Abstract: Acquired resistance to HER2-targeted therapies occurs frequently in HER2 þ breast tumors and new strategies for overcoming resistance are needed. Here, we report that resistance to trastuzumab is reversible, as resistant cells regained sensitivity to the drug after being cultured in drug-free media. RNA-sequencing analysis showed that cells resistant to trastuzumab or trastuzumab þ pertuzumab in combination increased expression of oxidative phosphorylation pathway genes. Despite minimal changes in mitochondria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Our results indicated that FABP4 inhibited the expression of CPT-1 (Figure 6D). Oligomycin A, an ATP synthase inhibitor, 37 was found to dose-dependently inhibit ATP production in macrophages (Figure S8B). Further study showed that oligomycin A markedly inhibited the activity of NF-κB/RelA translocation and the downstream IL1α concentration, which were induced by knocking-down FABP4 (Figure 6E and F).…”
Section: Atpb Is Associated With Fabp4-regulated Nf-κb Activation In Macrophagesmentioning
confidence: 97%
“…Our results indicated that FABP4 inhibited the expression of CPT-1 (Figure 6D). Oligomycin A, an ATP synthase inhibitor, 37 was found to dose-dependently inhibit ATP production in macrophages (Figure S8B). Further study showed that oligomycin A markedly inhibited the activity of NF-κB/RelA translocation and the downstream IL1α concentration, which were induced by knocking-down FABP4 (Figure 6E and F).…”
Section: Atpb Is Associated With Fabp4-regulated Nf-κb Activation In Macrophagesmentioning
confidence: 97%
“…Resistant cells were sensitive to inhibition of ATP synthase by oligomycin, and knockdown of F6 or β subunits rendered resistant cells responsive to a low dose of trastuzumab. Furthermore, combining ATP synthase inhibitor oligomycin with trastuzumab led to regression of trastuzumabresistant tumours in vivo (Gale et al 2020). A recent work on non-small-cell lung cancer cells subjected to X-ray irradiation showed that the expression level of the α subunit of ATP synthase is increased 24-96 h post-irradiation and that this is in line with an increased ATP hydrolysis in irradiated cells.…”
Section: Epigenetic Modulation Of Atp Synthase Induces Drug Resistancementioning
confidence: 96%
“…In one recent study, the oxidative phosphorylation gene signature was found to be enriched in trastuzumab‐resistant cells, which were sensitive to inhibition of ATP synthase by oligomycin A and knockdown components of the ATP synthase complex; this resulted in the responsiveness of resistant cells to a low dose of trastuzumab. ATP synthase plays a pivotal role in the oxygen metabolic process, which may also be implicated in regulating CD44 high /CD24 low /EpCAM + BCSCs and thus regulating trastuzumab resistance in HER2‐positive breast cancer 89 . Cirenajwis et al revealed that PG11047 could lead to the decrease of approximately 50% of CD44 + /CD24 −/low BCSCs by targeting the polyamine metabolic pathway and inhibiting BCSC‐like properties, 90 but further studies are required to explore its function in vivo.…”
Section: Bcsc‐targeted Therapeutic Approaches For Overcoming Trastuzumab Resistancementioning
confidence: 99%